ITIND: the second-generation temporary implantable nitinol device for minimally invasive treatment of benign prostatic hyperplasia. (June 2020) - Balakrishnan, Dhivya; Jones, Patrick; Somani, Bhaskar K.
ITIND is the second-generation version of the temporary nitinol implantable device (TIND), which has emerged over the past decade as one of the latest additions to the library of minimally invasive surgeries now available to treat bothersome lower urinary tract symptoms (LUTS) caused by benign prostate enlargement. While the key procedural steps remain the same, it now carries specific modifications designed to improve its efficacy and safety profile further. With the option to perform implantation under local anaesthesia, it can be delivered on an ambulatory basis and in the office setting. While the formal position of iTIND in current guidelines is yet to be determined, 12-month data demonstrates that it can improve both objective and subjective outcome measures, which are sustained at short-term follow up.